Lower Socioeconomic Status Is Associated With Worse Preoperative Function, Pain, and Increased Opioid Use in Patients With Primary Glenohumeral Osteoarthritis. Issue 7 (1st April 2020) - Sheth, Mihir M.; Morris, Brent J.; Laughlin, Mitzi S.; Elkousy, Hussein A.; Edwards, Thomas Bradley
Abstract : Background: Numerous studies have identified differences in patient-reported outcome scores and complication rates based on various measures of socioeconomic status (SES); however, there is limited information regarding the role of SES in the shoulder arthroplasty cohort. The purpose of this study was to characterize the role of SES in patients undergoing primary anatomic total shoulder arthroplasty (TSA) for primary glenohumeral osteoarthritis (OA). Methods: We identified 1, 045 patients who had primary TSA done for OA in a prospective shoulder arthroplasty registry, and 982 patients met inclusion criteria. We prospectively assessed patient demographics, comorbidities, patient-reported outcome scores, range of motion, and preoperative opioid use. Each patient was assigned to a quartile according to the Area Deprivation Index using their home address as a measure of SES. Results: The most disadvantaged patients (lower SES) reported to our center with a higher body mass index and higher rates of preoperative opioid use and diabetes. Patients in the most disadvantaged quartile reported more preoperative pain (Constant—Pain and American Shoulder and Elbow Surgeons [ASES]—Pain) and lower function (Constant—ADL, Constant—Total, and ASES). Multivariate regression identified that male patients and advanced age at surgery had better reported ASES pain scores, while preoperative opioid use, chronic back pain, and the most disadvantaged quartile were associated with worse ASES pain scores. Conclusion: Lower SES correlates with worse preoperative function and pain in patients undergoing anatomic TSA for primary glenohumeral OA. Providers should be cognizant of the potential impact of SES when evaluating quality metrics for patients with primary glenohumeral OA. Level of Evidence: Level 3, cross-sectional study.